Randomized Study of Collagen Cross-Linking With Conventional Versus Accelerated UVA Irradiation Using Riboflavin With Hydroxypropyl Methylcellulose: Two-Year Results. Issue 2 (February 2019) - Hagem, Anne Marie; Thorsrud, Andreas; Sandvik, Gunhild Falleth; Drolsum, Liv
Abstract : Purpose: To compare the clinical outcome 2 years after corneal collagen cross-linking (CXL) with conventional and accelerated ultraviolet A (UVA) irradiation using riboflavin with hydroxypropyl methylcellulose. Methods: Prospective randomized controlled study. Forty patients with keratoconus (40 eyes) were randomized to either CXL using conventional 3 mW/cm 2 UVA irradiation for 30 minutes (CXL30 group) or accelerated 9 mW/cm 2 UVA irradiation for 10 minutes (CXL10 group). In both groups, a solution of 0.1% riboflavin with 1.1% hydroxypropyl methylcellulose (methylcellulose–riboflavin) was used. Uncorrected distance visual acuity, corrected distance visual acuity (CDVA), and Scheimpflug tomography were performed at baseline and after 24 months. Results: Both groups had statistically significant improvement in CDVA and maximum keratometric reading compared with baseline; however, with no statistically significant difference in the change between the 2 groups. No significant changes in flattest, steepest and mean keratometry (K1, K2 and K mean) were found in either of the groups. There were no statistically significant changes in ECD in either group after 2 years or in the difference in the change between the 2 groups. A literature review showed comparative clinical outcome after accelerated CXL compared with conventional CXL; however, in several studies, there was a tendency for less pronounced corneal flattening after accelerated CXL. Conclusions: Improvement in visual acuity and maximum keratometric reading 2 years after CXL was found after both conventional and accelerated UVA irradiation using methylcellulose–riboflavin. This suggests that when using riboflavin with methylcellulose, the less time-consuming accelerated protocol is a valuable and effective option in CXL treatment.